Selected Stories of Oscar Wilde : masterpiece of world fiction - Brien, Terry O' (New Delhi : Rupa, 2014)
The Masterpieces of World Fiction series brings together the best-loved short stories by the great masters of the genre from Chekov and Maupassant, Kipling and Wilde, to O. Henry and Saki and Tolstoy and Conrad. Thoughtfully compiled by the bestselling author Terry O' Brien, this series is a great way for readers to revisit old favorites and for introducing literary masterpieces to newer, younger readers.
Keywords: Fiction; Short stories